Phytochemical analysis and antioxidant activities ethanol extract of propolis Trigona spp. from different vegetation in Lombok, West Nusa Tenggara, Indonesia - KUNTI TIRTASARI; LUCIA TRI SUWANTI; MUFASIRIN MUFASIRIN; POEDJI HASTUTIEK; ELLY NUR INDASARI; ROCHMAH KURNIJASANTI; HANI PLUMERIASTUTI; ERMA SAFITRI; EKA PRAMYRTHA HESTIANAH (Society for Indonesian Biodiversity, 2024)
Abstract. Tirtasari K, Suwanti LT, Mufasirin, Hastutiek P, Indasari EN, Kurnijasanti R, Plumeriastuti H, Safitri E, Hestianah EP. 2024. Phytochemical analysis and antioxidant activities ethanol extract of propolis Trigona spp. from different vegetation in Lombok, West Nusa Tenggara, Indonesia. Biodiversitas 25: 404-411. Propolis is a natural substance containing a resin that is collected by honey bees from various plants and has a significant effect on human health such as antibacterial, antifungal, anti-inflammatory, antiviral, anesthetic, antioxidant, antitumoural, antiprotozoal, anticancer, antihypertensive, anticarcinogenic, antihepatotoxic and has cytotoxic activity. Cultivation of Trigona spp. in Lombok is growing rapidly. Trigona spp. produces more propolis than honey bees of Apis spp., but bee products that are maximally utilized are only honey, and propolis has not been utilized optimally. Currently, there is no scientific validation of the phytochemical content, bioactive compounds, and biological activities of ethanol extract propolis Trigona spp. from Lombok, West Nusa Tenggara. So, this study aimed to determine the phytochemical compounds, bioactive compounds, and antioxidant activity of propolis. Gas Chromatography-Mass Spectrometry (GC-MS) analysis was performed to determine the bioactive compounds of ethanol extract propolis. DPPH (2,2-diphenyl-1-picrylhydrazyl) was used to evaluate antioxidant activity. The composition of propolis compounds is different for each propolis depending on the bee species and the vegetation source from which the resin was collected. In this research, propolis was collected from different vegetation sources (cashews, moringa, coffee, and lote trees). This study used qualitative and quantitative phytochemical analysis and the antioxidant DPPH test. Different components and percentages cause significant variations in the results obtained from phytochemical tests. The content is different in various propolis, there are saponins, flavonoids, and tannins. The highest antioxidant activity was found in propolis with moringa resin 38.4150 (very strong), followed by lote tree resin -66.0420 (strong), cashew resin 81.8140 (strong), and coffee resin 100.7465 (moderate).